Metodologi Studi Hadis JamÃ¢l al-BannÃ¢ - Zamzami, Mukhammad (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2014)
Text will always interacting with the context. He always dialectic with the conditions in which the text was born. Therefore, to understand a text, an understanding about the context becomes a necessity that must be done, not least the understanding of hadith texts. Without understanding a variety of variables and circumstances behind the text that includes historical aspects, sociological, psychological, and so on, then this will potentially misinterpretation. This article explores the ideas of Jamal al-Banna on the methodology of contemporary traditions. He offers concepts and methodologies so resolutive and intelligent in understanding the Sunnah of the Prophet. He also shows how Muslims should ideally interact with the Sunnah. Departing from the description, it will be explored in this article about Jamal al-Banna Sunnah thinking which will then be analyzed in this hermeneutic perspective. According to him, Muslims today should make the Sunnah as a model of ijtihad, which also means keeping the existence of Sunnah. That is, people now have to follow the path and methodology, not the spoken word; follow the Sunnah of the Prophet, do not follow the text of the hadith.